Developing an Artificial Intelligence (A.I)‐based descriptor of facial appearance that fits with the assessments of makeup experts. Issue 6 (17th May 2021) - Flament, Frederic; Zhang, Yuze; Yu, Zhi; Jiang, Ruowei; Houghton, Jeff; Sarda Duthil, Lauren; Arcin, Vincent; Daniel, Raja; Perrier, Jean‐Charles; Niviere, Joel; Moyano, German; Thenin, Audrey; et al.
Abstract: Objective: To develop an A.I‐based automatic descriptor that detects and grades, from selfie pictures, 23 facial signs, hairs included, as a help to making‐up procedures. Material and Methods: The selfie images taken in very different conditions by 3326 women and men were used to create (90% of dataset) and validate (10% of dataset) a new algorithm architecture to appraise and grade 23 different facial signs such as lips, nose, eye color, eyebrows, eyelashes, and hair color as defined by makeup artists. Each selfie image was annotated by 12 experts and defined references to train Artificial Intelligence (A.I)‐based algorithm. Results: As some the 23 signs present a continuous or discontinuous feature, these were analyzed by two different statistical approaches. The results provided by the automatic descriptor system were not only in good agreement with the expert's assessments but were even found of a better precision and reproducibility. This automatic descriptor system has proven a good and robust accuracy despite the very variable conditions in the acquisition of selfie pictures. Conclusion: Such automatic descriptor system seems providing a valuable help in making‐up procedures and may extend to other activities such as Skincare or Haircare. As such it should allow large investigations to better evaluate the consumers' needs of esthetical improvements.